Extended Writing Performance and Higher-Order Thinking Skills via Flipped Learning - Kernagaran, Vanhitha; Abdullah, Amelia (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2025)
This study investigates the impact of process writing and flipped learning on enhancing students' extended essay writing performance and higher-order thinking skills (HOTS). The process writing approach emphasises writing as a recursive activity involving multiple drafts, feedback, and revisions to improve coherence and clarity. A quasi-experimental design was applied, involving 120 Form Four students in northern Malaysia. Participants were divided into an experimental group, which received process writing-based flipped learning instruction, and a control group, which received textbook-based instruction in a flipped setting. Data were collected through pre-test and post-test assessments of writing and HOTS, along with qualitative feedback from student interviews. Analysis of covariance (ANCOVA) revealed significant improvements in the experimental group's writing across content, communicative achievement, organisation, and language use. Additionally, the experimental group showed marked growth in HOTS, particularly in analysing, evaluating, and creating. Although originally proposed in 1981, Flower and Hayes' model remains relevant for understanding the cognitive processes involved in students during writing, especially in instructional design contexts. This study supports the integration of process writing and flipped learning to enhance writing performance and HOTS, offering practical insights for educators seeking an effective and engaging instructional approach in teaching and learning of extended essay writing.